Flexible Room‐Temperature Ammonia Sensor Using Multi‐Heterojunction MoO3/CuO/Cu2O Nanoclusters for Noninvasive Kidney Disease Diagnosis - Haoyu Qian; Wenjing Yan; Yingzhu Li; Xingquan Zhou; Shengjie Xia; Yuyuan Qin; Peng Mao; Bo Xie; Min Han; Jun Hu (Small Structures)
In this study, a flexible room‐temperature ammonia (NH3) sensor is developed based on MoO3/CuO/Cu2O hybrid nanoclusters (HNCs), specifically designed for the noninvasive diagnosis of nephropathy. The MoO3/CuO/Cu2O HNCs achieve an ultralow detection limit of 0.73 ppm, with high sensitivity (0.163 ppm−1) and rapid response and recovery times (16.4 and 90.6 s). The integration of MoO3 (n‐type) with CuO and Cu2O (p‐type) forms multi‐heterojunctions, enhancing gas‐sensing performance through efficient charge separation and improved NH3 adsorption. Additionally, the sensor demonstrates excellent mechanical flexibility and long‐term stability under dynamic deformation. To address humidity interference in exhaled breath analysis, the sensor with a hydrophobic polytetrafluoroethylene layer is coated via radio frequency sputtering, ensuring effective NH3 detection and differentiation between healthy individuals and kidney disease patients. In this work, the potential of multi‐heterojunction nanostructures in developing high‐performance, flexible gas sensors for practical health‐monitoring applications is highlighted.